E-Beam evaporation을 이용한 전극 형성 공정이 결정질 실리콘 태양전지에 미치는 영향 분석 - 최동진(Dongjin Choi); 박세진(Se Jin Park); 신승현(Seung Hyun Shin); 이창현(Changhyun Lee); 배수현(Soohyun Bae); 강윤묵(Yoonmook Kang); 이해석(Hae-Seok Lee); 김동환(Donghwan Kim) (Current Photovoltaic Research, 2019)
Most high-efficiency n-type silicon solar cells are based on the high quality surface passivation and ohmic contact between the emitter and the metal. Currently, various metalization methods such as screen printing using metal paste and physical vapor deposition are being used in forming electrodes of n-type silicon solar cell. In this paper, we analyzed the degradation factors induced by the front electrode formation process using e-beam evaporation of double passivation structure of p-type emitter and $Al_2O_3/SiN_x$ for high efficiency solar cell using n-type bulk silicon. In order to confirm the cause of the degradation, the passivation characteristics of each electrode region were determined through a quasi-steady-state photo-conductance (QSSPC).